Legal Responsibility for Negligence Performed by Doctors Specialist Education Doctors Programs - Muhammad Rizaldy Hariansyah; Slamet Sampurno; Nur Azisah (Soepra: Jurnal Hukum Kesehatan, 2021)
Abstract: This study aims to understand the legal position of PPDS doctors in health services in hospitals and to determine the legal responsibility to patients for medical negligence carried out by PPDS doctors. Research The legal material collection technique used in this writing is carried out with library research, namely the study of books, scientific papers, theses, dissertations, encyclopedias, the internet, and other sources. To complete the information needed, interviews were conducted with informants selected based on the capacity and authority carried out by the informants related to this writing.